ПЗС-фотоматрицы с электронным умножением - Рева, В.П.; Коринец, С.В.; Голенков, А.Г.; Сапон, С.В.; Торчинский, А.М.; Забудский, В.В.; Сизов, Ф.Ф. (Технология и конструирование в электронной аппаратуре, 2017)
Описаны принципы работы фотоматриц видимого излучения и ближнего инфракрасного диапазона, спроектированных на основе приборов с зарядовой связью с электронным умножением (ПЗС-ЭУ), и обсуждена архитектура построения таких матриц. Приведено краткое описание технологии изготовления фотоматриц ПЗС-ЭУ, а также некоторые параметры спроектированных и изготовленных экспериментальных образцов фотоматриц формата 640×512. Описано принципи роботи фотоматриці видимого випромінювання і ближнього інфрачервоного діапазону, спроектованих на основі приладів із зарядним зв'язком з електронним множенням (ПЗЗ-ЕМ), та обговорено архітектуру побудови таких матриць. Наведено короткий опис технології виготовлення фотоматриці ПЗЗ-ЕМ, а також деякі параметри спроектованих і виготовлених експериментальних зразків фотоматриці формату 640×512. Electron multiplication charge coupled devices (EMCCD) technology is an innovation first introduced slightly more than a decade ago. The EMCCD is an image sensor that is capable of detecting an isolated photon without an image intensifier. It is achieved by electron multiplication circuit that is built in the chip of ordinary CCD. Cameras with EMCCD arrays overcome limitations of getting high sensitivity with high frame rate. Traditional CCD cameras can be highly sensitive in the visible part of spectrum but at the expense of low frame rate. EMCCD can operate at very faint illumination conditions both in visible and near infrared regions. The paper presents a short technological description of EMCCD 640×512 arrays manufacturing and some parameters of the arrays that were designed and manufactured. It was shown that multiplication coefficient depends much on applied amplification voltage and can achieve 1000. Also it is shown that images can be obtained at low illumination conditions (illumination at EMCCD is near 5∙10⁻⁴ lx).